Unusual Presentation of Acute Annular Urticaria: A Case Report - Gilles Guerrier; Jean-Marc Daronat; Roger Deltour (Case Reports in Dermatological Medicine)
Acute urticarial lesions may display central clearing with ecchymotic or haemorrhagic hue, often misdiagnosed as erythema multiforme, serum-sickness-like reactions, or urticarial vasculitis. We report a case of acute annular urticaria with unusual presentation occurring in a 20-month-old child to emphasize the distinctive morphologic manifestations in a single disease. Clinicians who care for children should be able to differentiate acute urticaria from its clinical mimics. A directed history and physical examination can reliably orientate necessary diagnostic testing and allow for appropriate treatment.